Distribution of nickel (Ni) in peatland situated alongside mineral soil derived from ultrabasic rocks - Heru Bagus Pulunggono; Moh Zulfajrin; Fuadi Irsan (Universitas Sebelas Maret, 2021)
Detailed studies of Ni distribution in peat that is influenced by Ni-rich soil derived from ultrabasic rocks are still limited. The objective of this study was to reveal the characteristics of Ni in peat from Morowali (Central Sulawesi Province, Indonesia) at several depths and distances from the boundary of the ultrabasic mineral soil. Peat was sampled from depths of 0–30, 30–60, and 60–90 cm at distances of 100, 200, 300, 400, 500, and 600 m from the border of the ultrabasic mineral soil in March 2018. Ni characteristics were examined through their total, exchangeable, water-soluble, and adsorbed distributions. The relationships between Ni and some peat chemical properties such as pH; cation exchange capacity; macronutrient contents of K, Ca, and Mg; and micronutrient contents of Fe, Cu and Zn were also observed. The high Ni content in peat at the study transect is caused by an accumulation of Ni transported from elevated areas of mineral soil. Most Ni in peat is bonded to the soil organic exchange complexes. Accumulation of the mineral soil fraction in the peat surface is indicated at distances of 100–400 meters from the ultrabasic mineral soil. Ni distribution in peat at the study transect is mainly governed by a combination of Fe, pH, organic material, water content, peat depth, and distance from ultrabasic mineral soil.